2009
DOI: 10.1111/j.1758-2229.2009.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

South American native bumblebees (Hymenoptera: Apidae) infected by Nosema ceranae (Microsporidia), an emerging pathogen of honeybees (Apis mellifera)

Abstract: As pollination is a critical process in both human-managed and natural terrestrial ecosystems, pollinators provide essential services to both nature and humans. Pollination is mainly due to the action of different insects, such as the bumblebee and the honeybee. These important ecological and economic roles have led to widespread concern over the recent decline in pollinator populations that has been detected in many regions of the world. While this decline has been attributed in some cases to changes in the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(125 citation statements)
references
References 20 publications
(45 reference statements)
3
118
0
4
Order By: Relevance
“…Nosema ceranae is traditionally thought of as being a honeybee parasite and has been implicated in colony losses in some areas [31][32][33]. However, N. ceranae has more recently been identified as an emerging pathogen in several bumblebee species, causing both lethal and sublethal effects [22,37,39,40]. The results here highlight the potential role of shared flower use as a mode of transmission, which will facilitate the spillover of harmful parasites between different pollinators and populations.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Nosema ceranae is traditionally thought of as being a honeybee parasite and has been implicated in colony losses in some areas [31][32][33]. However, N. ceranae has more recently been identified as an emerging pathogen in several bumblebee species, causing both lethal and sublethal effects [22,37,39,40]. The results here highlight the potential role of shared flower use as a mode of transmission, which will facilitate the spillover of harmful parasites between different pollinators and populations.…”
Section: Discussionmentioning
confidence: 78%
“…Importantly, there is increasing evidence of parasite transmission between pollinator taxa being more significant than has generally been appreciated. Several honeybee viruses and the N. ceranae microsporidian parasite of honeybees have been detected infecting bumblebees [22,[35][36][37][38][39][40][41][42], and the Apicystis bombi neogregarine parasite of bumblebees has been shown experimentally to infect honeybees [22,43].…”
Section: Introductionmentioning
confidence: 99%
“…Plischuk et al (2009) described the presence of N. ceranae in three species of Argentine native bumblebees. In Colombia, bumblebees were found to be infected by at least four different species of pathogens.…”
Section: Nosemosismentioning
confidence: 99%
“…Moreover, Klee et al (2007) reported that N. ceranae is a disease of global proportions detected in many parts of the world, including Europe, Africa, Asia, America and Oceania (Higes et al 2006, Calderón et al 2008, Giersch et al 2009b , Chen and Huang 2010. In South America, studies have confirmed the presence of N. ceranae in Brazil (Texeira et al 2013), Uruguay (Invernizzi et al 2009), Argentina (Plischuk et al 2009, Medici et al 2012 and Chile (Martínez et al 2012, Rodríguez et al 2012.…”
Section: Discovery and Geographical Distributionmentioning
confidence: 77%
“…However, recent studies have shown that N. ceranae has changed its feeding habits and is no longer unique to the eastern bee, but has also become a very efficient parasite of european bees , Chen et al 2008 and several species of bumblebees (Plischuk et al 2009, Li et al 2012, Graystock et al 2013. The resulting disease is known as type C nosemosis (Higes et al 2010 b ).…”
Section: Introductionmentioning
confidence: 99%